The clinical task force: Improving quality of medical students' internship. Issue 2 (February 2023) - Baker, J.J.; Weis, N.; Boysen, T.; Bestle, M.H.; Andersen, A.G.; Morcke, A.M.; Bremholm, L.
Abstract: Background: Up to 40% of young medical doctors feel that the internships prepared them insufficiently for the clinical work. This study investigated whether a Clinical Task Force (CTF) could improve internship quality. Methods: The CTF visited internship departments with a triple-targeted approach: first, departments pre-filled a self-evaluating questionnaire; secondly, CTF visited departments to discuss the self-evaluation and previous student evaluations; and thirdly, CTF and departments agreed on several quality-improving focus points to work on after the meeting. Focus points were followed-up after three and 12 months. The impact on internship quality was assessed with departments' student evaluation scores, number of completed focus points, and the effect of completed focus points on a range of learning parameters. The CTF learned several things along the way, that potentially could affect the quality of internships. A shortlist of these was provided to illustrate unmeasurable benefits. Results: The CTF met with 53 out of 60 eligible departments. The CTF and departments agreed upon 197 focus points of which 64% were completed. The three most frequent categories of focus points were Introduction of the students, The departments' evaluation percentage, and The departments' function as an educational site. The mean student evaluation scores did not change significantly, but the individual evaluation parameters changed significantly in two categories. It decreased in the category regarding the students' satisfaction with the clinical lecturers and the scheduled teaching and increased in the category regarding the percentage of students evaluating the department. Conclusion: The CTF's triple-targeted approach did not increase the mean student evaluation score significantly. For departments that completed the agreed focus points, one category increased and another decreased. However, the unmeasurable benefits illustrated that CTF was a good viable linking element between the faculty, departments, and students with the potential of improving other aspects of the quality of internships.